A framework for exploring the stage of public response on Social Media Sites (SMSs) towards social enterprise in Malaysia / Nik Fakrulhazri Nik Hassan ... [et al.] - Nik Hassan, Nik Fakrulhazri; Ahmad, Noorazlina; Abu Kassim, Abd Razak; Mohd Sallem, Nur Raihana (Universiti Teknologi MARA, Perlis, 2021)
Social enterprise is popular among researchers because of its contribution and prominence in society. Many entrepreneurs seek to create ventures that not only yield a profit but also add value to society. However, previous studies have found that the level of public awareness of the existence of social enterprises is still low and at an early stage. Thus, they suggest the use of social media as an alternative way to attract attention and create public awareness on social enterprise in Malaysia. This concept paper seeks to explore the stages of public responses to existing social enterprise in Malaysia and discover the role of social media in terms of enhancing social enterprise awareness and promoting social enterprise. There are three stages of public responses used in this concept paper which are 'aware', 'interested' and 'engaged'. Essentially, this concept paper attempts to provide the first insight regarding the stage of social enterprise awareness in Malaysia and to recognize the vital elements in social media sites. To enhance public awareness toward social enterprise existing, this concept paper proposes a storytelling canvas as a support tool to spark the effects of the vital elements. Data could be retrieved from social media (Facebook and Twitter). For data analysis and data management, this paper proposes to use Nvivo to develop the framework and flow of data collection. The expected results can add more value to the theories and identify the stage of public responses towards social enterprise business activities and their social mission.